2013
DOI: 10.1309/ajcp1rf9fuizrdpi
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver Concordance in Implementing the 2010 ASCO/CAP Recommendations for Reporting ER in Breast Carcinomas

Abstract: Discordance overwhelmingly reflected differing opinions recording the proportion of tumor cells positive with low levels of expression (<10% staining; 12/13 cases).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 20 publications
1
15
2
Order By: Relevance
“…Therefore, the true differences in tumor genomics can be confounded by these two factors. However, a review of the prior literature [37, 38] shows that heterogeneity found in our study is notably higher than found in the studies related to observer variability. Therefore, a minor part of the variability comes from the interobserver/technique induced variability and the majority of the differences are from inter-sample variability.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Therefore, the true differences in tumor genomics can be confounded by these two factors. However, a review of the prior literature [37, 38] shows that heterogeneity found in our study is notably higher than found in the studies related to observer variability. Therefore, a minor part of the variability comes from the interobserver/technique induced variability and the majority of the differences are from inter-sample variability.…”
Section: Discussioncontrasting
confidence: 88%
“…Therefore, a minor part of the variability comes from the interobserver/technique induced variability and the majority of the differences are from inter-sample variability. For example, in our study, 8.78% of average discordance between a pair of samples for the patients was observed using positivity/negativity for ER percentage staining which is greater than the discordance (<5%) seen between the observers in the study by Reisenbichler et al [38]. Moreover, using ER Allred score, a difference of more than 1 point in 20.62% percent of the cases was found whereas Reisenbichler et al found that occurring in less than 10% of their cases.…”
Section: Discussioncontrasting
confidence: 72%
“…These results are comparable with other groups that have evaluated inter-observer agreement for estrogen receptor immunohistochemical assays. 24,25 To our knowledge, ours is the only study that also evaluated intra-observer agreement. Three months after initial review, Observers 1 and 3 rescored the tissue microarray slides and we found strong agreement across all platforms (Îș ≄ 0.91).…”
Section: Discussionmentioning
confidence: 98%
“…Beside different scoring systems interobserver variability can also occur. Tumors with low levels of ER expression are often difficult to classify and can lead to observer discordance [24]. In our study the scoring results of the central lab using the Allred scoring method and those of the participating lab using their proper scoring system were significantly positive correlated for ER and PR.…”
Section: Discussionmentioning
confidence: 47%